Exploring the green purchase intention-behavior gap among South African millennials using an expanded planned behavior model - Boitumelo Mabaso; Christian Nedu Osakwe; Abdul Bashiru Jibril (Cogent Business & Management)
This study investigates the determinants of green purchase behaviour among South African millennials, drawing on a sample of 189 respondents to elucidate the most salient antecedents that drive green consumption within this demographic. Anchored in an extended Theory of Planned Behavior (TPB), the research incorporates environmental concern and personal norms as additional predictors of favourable attitudes toward green products, while also assessing whether willingness to pay a premium and perceived consumer effectiveness moderate the intention-behaviour relationship. Employing partial least squares factor-based structural equation modeling (PLSF-SEM), the analysis reveals that both environmental concern and personal norms exert a significant positive influence on consumers’ attitudes, which, in turn, emerge as robust predictors of green purchase intention. Furthermore, intention was found to significantly predict actual green purchase behaviour. Contrary to expectations, subjective norms did not exert a meaningful effect on green purchase intentions, and the hypothesised moderating roles of willingness to pay and perceived consumer effectiveness were not empirically supported. These findings contribute to the growing discourse on green consumption in particular and eco-conscious behavior in general by highlighting the primacy of internalized values and attitudes over social influence or economic considerations in shaping green/eco-conscious behaviours among millennial consumers in emerging markets.